The tribes in the field of servitization : Discovering latent streams across 30 years of research - Rabetino, Rodrigo; Kohtamäki, Marko; Brax, Saara A.; Sihvonen, Jukka (Elsevier, 2021)
The servitization domain consists of over three decades of multi-disciplinary research on service activities in industrial contexts. Servitization literature combines different research streams that share a set of critical concepts. Existing meta-analytical studies have organized information content of sub-streams, homogenized theoretical propositions, and concepts to discover shared patterns, and identified an implicit meta-narrative. This study reverses the meta-analysis direction to deconstruct the servitization body of knowledge using the dynamic topic modeling (DTM) methodology to analyze 550 research articles. DTM enables complex forms of content analysis that combine quantitative and qualitative analysis. The analysis demonstrates how these streams have informed the development of the servitization domain and shaped the collective construction of this body of knowledge. The contributions of this study are threefold. First, the study increases understanding of the conceptual dynamics and thematic trends within the servitization research domain and the nuances between the sub-streams. The study offers some strategies for the future development of the field, facilitating the renewal of the servitization-related research agenda. Second, it illustrates the role of DTM as an alternative tool for conducting a literature review. Finally, it supports the development of a common language for the servitization field, thereby reducing the entry barriers for new contributors and favoring the knowledge transfer to professionals.
Keywords: Servitization; Topic modeling; Narratives; Literature review; fi=Strateginen johtaminen|en=Strategic Management|